2017
DOI: 10.1002/chem.201606031
|View full text |Cite
|
Sign up to set email alerts
|

Role of Halide Ions in the Nature of the Magnetic Anisotropy in Tetrahedral CoII Complexes

Abstract: A series of mononuclear tetrahedral Co complexes with a general molecular formula [CoL X ] [L=thiourea and X=Cl (1), Br (2) and I (3)] were synthesized and their structures were characterized by single-crystal X-ray diffraction. Direct-current (dc) magnetic susceptibility [χ T(T) and M(H)] and its slow relaxation of magnetization were measured for all three complexes. The experimental dc magnetic data are excellently reproduced by fitting both χ T(T) and M(H) simultaneously with the parameters D=+10.8 cm , g =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 90 publications
3
45
0
Order By: Relevance
“…70,71 In the above context, the coordination of heavier halogeno ligands to Ni(II) 72 or Cr(II) 73 has been shown to confer increased axial anisotropies. Similar effects, on the magnitude of the axial anisotropy due to the coordination of heavier halides, have also been established in tetrahedral [74][75][76][77][78][79][80] Co(II) complexes, in some instances imposing a concomitant change in the sign of D as well. 76,77 On the other hand, contrary to the above observations, lower axial anisotropy due to the coordination of heavier halides has been observed in squarepyramidal 81,82 and pentagonal bipyramidal 83 Co(II) complexes.…”
Section: Effects Of S/se Metal-coordinationsupporting
confidence: 64%
“…70,71 In the above context, the coordination of heavier halogeno ligands to Ni(II) 72 or Cr(II) 73 has been shown to confer increased axial anisotropies. Similar effects, on the magnitude of the axial anisotropy due to the coordination of heavier halides, have also been established in tetrahedral [74][75][76][77][78][79][80] Co(II) complexes, in some instances imposing a concomitant change in the sign of D as well. 76,77 On the other hand, contrary to the above observations, lower axial anisotropy due to the coordination of heavier halides has been observed in squarepyramidal 81,82 and pentagonal bipyramidal 83 Co(II) complexes.…”
Section: Effects Of S/se Metal-coordinationsupporting
confidence: 64%
“…on this complex predicted a very large negative D value of −70 cm −1 [9a] . Magneto‐structural correlations performed on this type of {CoS 4 } system by us and others further revealed that the magnetic anisotropy of these complexes is controlled by the following factors: i) structural parameters such as bond angle and torsional angle around the first and second coordination sphere atoms, [12c, 39] ii) effect of donor atoms or ligand field strength, [39b, 40] iii) spin‐orbit coupling of the donor atoms [41] and also iv) counterions [39d, 42] . Soft donor groups such as S, Se/Br, I coordination bring down the 4 A 2 → 4 T 2 (ligand field states in T d symmetry) transition energy gap, and thus the D switches to negative from positive.…”
Section: Zero‐field Splitting In Transition Metal‐based Simsmentioning
confidence: 69%
“…The energy gap betweent he Y 1 and Y 3 orbitals and Y 2 and Y 3 orbitals are very similar in both the complexes which is expected from the similart orsional angle (q t )i nc omplex 1 (100 and 1018)a nd complex 2 (97 and 998). Figure 10 represents the D and g anisotropy axes of complexes 1 and 2.T he structuralp arameter which controlst he D value is the O-Co-Oo rt orsion angle [33] while the E/D value is controlled by the interplanar or dihedrala ngle [34] (Table 2). Both complexes 1 and 2 have very similart orsion angles which explains the closeness of the D values.…”
Section: Resultsmentioning
confidence: 99%